Regarding the Use of Direct-Acting Anticoagulants of Animal Origin in Diabetic Retinopathy - I. V. Vorobyeva; V. V. Biryukov; M. A. Frolov; A. M. Frolov; U. S. Pliaskina; S. Shallah (Oftalʹmologiâ)
Relevance. Diabetic retinopathy occupies one of the leading places in the frame of blindness and low vision. The very first changes in the retina in diabetic retinopathy are disorders of microcirculation and blood supply in the small vessels of the macula. There are few effective drugs that can restore perfusion in the small retina’s vessels. In this connection, it is relevant to search for anticoagulants that allow restoring blood supply in the macular area in diabetic retinopathy in the early stages.The purpose. To analyze the research of a domestic direct-action anticoagulant from animals, a drug of the heparin group Pyavit, both in ophthalmology for diabetic retinopathy and in other fields of medicine. The analysis of publications on eLibrary and PubMed resources for the last 30 years was done, by the keywords: direct-acting anticoagulants, diabetic retinopathy, hirudins, hemodynamics, optical coherence tomography (OCT), hemostasis. The data on the study and application of the drug from its development to its use in diabetic retinopathy, retinal vascular pathology, and pregnancy was analyzed. Researchers have studied the importance of the salivary gland secretion of a medical leech, which is a regulator of the hemostasis system. In 1992 I.P. Baskova patented a new drug Pyavit, which is officially approved for use in medical practice (registration number No. 000363/02). Dosage regimen: 300 mg three times a day for 20 days, and repeat the course through 1–2 months. In ophthalmology, researchers have proven the positive effect of the drug on the retina in diabetic retinopathy with an improvement in visual acuity, retinal thickness according to objective indicators of optical coherence tomography, fluorescence angiography, and hemostasis system.Conclusion. The analysis of scientists’ research allows us to expand knowledge about the positive effect of the drug Piavit on the path of diabetic retinopathy. Based on this review, the authors plan to further study the drug, which will assess the importance and significance of improving microcirculation in the macular area of the retina using the anticoagulant Pyavit to preserve visual functions.